The Herb-Drug Interaction of Clopidogrel and Xuesaitong Dispersible Tablet by Modulation of the Pharmacodynamics and Liver Carboxylesterase 1A Metabolism. (18th October 2018) - Ma, Shitang; Dai, Guoliang; Bi, Xiaolin; Gong, Meirong; Miao, Chenggui; Chen, Hao; Gao, Liangliang; Zhao, Weiman; Liu, Tianjun; Zhang, Ningru
Abstract : Objective . Clopidogrel and Xuesaitong dispersible tablet (XST) have been clinically proven to be effective for treating cardiocerebrovascular disease. The present study was to investigate the herb-drug interaction of Clopidogrel and XST by modulation of the pharmacodynamics and liver Carboxylesterase 1A(CES1A) metabolism. Methods . 30 male SD rats were randomly divided into a control group (equal volumes of saline, 6 rats for mRNA analysis), a clopidogrel group (clopidogrel with dose 30 mg/kg), and a combination group (clopidogrel and XST, with dose 30 and 50 mg/kg respectively, each group continuous administration once daily for 30 days). The clopidogrel and combination group comprised 12 rats, with 6 designated for mRNA analysis and 6 for the pharmacokinetic study. The 2-bromo-3'-methoxyacetophenone- (MPB-) derivatized clopidogrel active thiol metabolite (CAMD) was measured by UHPLC-MS/MS for pharmacokinetics (n=6). The expression of CES1A mRNA was examined with real-time RT-PCR (n=6). Molecular simulation was used to investigate the inhibition effect of XST on the CES1A protein. The CAMD pharmacodynamics and CES1A metabolism were investigated to evaluated the herb-drug interaction. Results . Clopidogrel and XST coadministration appreciably increased the Cmax, AUC, and MRT of CAMD. However, the expression of CES1A mRNA was decreased accordingly. It also indicated that the bioactive components in XST had good interaction with the CES1A metabolism target by molecular simulation. The animal study indicated that clopidogrel and XST coadministration produced significant herb-drug interactions at active CAMD pharmacokinetic and CES1A metabolic enzyme aspect. Conclusion . 30-days dose of coadministration altered hepatic CES1A protein and resulted in reduced plasma levels of active CAMD. both the decreased CES1A mRNA expression and the inhibition on the protein were due to the combination of XST, which accordingly upregulated the pharmacokinetics of plasma active CAMD.